Rwanda : Interim Performance Update Under the Policy Coordination Instrument-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2020)
COVID-19 has had a severe economic impact on Rwanda through the implementation of strict domestic measures to contain the spread of the virus and the related global spillovers. The authorities have responded by rolling out health and economic measures totaling USD 311 million (3.3 percent of GDP) to mitigate the impact on businesses and households. To help address the urgent balance of payments need arising from the pandemic, the Executive Board approved on April 2 and June 11, 2020 the authorities' consecutive requests for emergency financing under the 'exogenous window' of the Rapid Credit Facility (RCF) totaling SDR 160.2 million (IMF Country Reports No. 20/115 and No 20/207). This brings the total IMF COVID-19 support to Rwanda to 100 percent of quota, or USD 220.46 million.